Anticipatory prescribing for end of life care in the community: a survey of community nurses in England - Wilson, Eleanor; Seymour, Jane (RCN Publishing, 2016)
Anticipatory prescribing is increasingly common in the UK, yet little is known about nurses’ roles in the process. As part of a wider study to explore this, a postal survey of 575 community/district, nursing home and palliative care nurses was undertaken in two regions. Nurses report anticipatory prescriptions to be very common, and once in place they are normally used. Findings show that nurses report taking prominent roles throughout the anticipatory prescribing process and principal responsibility for administering and monitoring the medications. Many respondents recount good working relationships with GPs. However, some nurses report being challenged by: GPs who are reluctant to prescribe the medications, incorrectly written prescriptions, and difficulties in gaining access to the necessary medications. Qualitative comments indicated that being a nurse prescriber could enhance confidence to use anticipatory prescriptions. Importantly, nurses responding to the survey perceived that anticipatory prescriptions facilitated provision of good end of life care.